PEMBUATAN APLIKASI OPTIMASI PENJUALAN PRODUK PADA TOKO LANCAR ABADI BLORA DENGAN MENGGUNAKAN METODE LINEAR PROGRAMMING METODE SIMPLEKS - Yonico Ariando Pratama; Dyah Erny Herwindiati; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
Every sale is bound to experience a problem. For example, the constraints of limited storage space, budget constraints and the number of goods sold. Toko Lancar Abadi Blora also experienced similar problems in selling its products, so that often the income generated from sales was less than optimal. Based on the above problems, a method in Operations Research is needed, namely Linear Programming, the Simplex Method to solve the above problems. Linear Programming Method Simplex method can determine the optimum value of a linear problem. In a linear problem there is a linear function which can be called an objective function or a constraint function. The requirements, constraints, and constraints in linear problems are systems of linear inequalities. The calculation accuracy of the Simplex method reaches 100% by comparison with the manual calculation of 12 trial cases that have been made with 12 different months. From these results it can be concluded that the Linear Programming method Simplex method can determine the optimum result of an inequality and can be applied in the sale of goods.